2020
DOI: 10.1172/jci121127
|View full text |Cite
|
Sign up to set email alerts
|

Off-the-shelf EBV-specific T cell immunotherapy for rituximab-refractory EBV-associated lymphoma following transplantation

Abstract: BACKGROUND. Adoptive transfer of donor-derived EBV-specific cytotoxic T-lymphocytes (EBV-CTLs) can eradicate EBVassociated lymphomas (EBV-PTLD) after transplantation of hematopoietic cell (HCT) or solid organ (SOT) but is unavailable for most patients. METHODS.We developed a third-party, allogeneic, off-the-shelf bank of 330 GMP-grade EBV-CTL lines from specifically consented healthy HCT donors. We treated 46 recipients of HCT (n = 33) or SOT (n = 13) with established EBV-PTLD, who had failed rituximab therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
193
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(199 citation statements)
references
References 52 publications
4
193
1
1
Order By: Relevance
“…In addition to therapeutic approaches using Treg cell infusion, another three clinical trials are underway with the aim of evaluating treatment using specific SARS-CoV-2 T cells isolated from individuals who recovered from COVID-19 (290)(291)(292). The use of virus-specific T cells for off-the-shelf treatment has been used in several viral infections, such as cytomegalovirus, HHV6, adenoviruses, Ebola virus, and BK virus (293)(294)(295)(296). Although vaccination provides T cells-based virus-specific immunity, the path to its development is long, so the use of adoptive cell transfer techniques from healthy individuals who recovered from COVID-19 and developed an effective cell response is probably the fastest way to treat critically ill individuals (297).…”
Section: Immune Cell-based Therapymentioning
confidence: 99%
“…In addition to therapeutic approaches using Treg cell infusion, another three clinical trials are underway with the aim of evaluating treatment using specific SARS-CoV-2 T cells isolated from individuals who recovered from COVID-19 (290)(291)(292). The use of virus-specific T cells for off-the-shelf treatment has been used in several viral infections, such as cytomegalovirus, HHV6, adenoviruses, Ebola virus, and BK virus (293)(294)(295)(296). Although vaccination provides T cells-based virus-specific immunity, the path to its development is long, so the use of adoptive cell transfer techniques from healthy individuals who recovered from COVID-19 and developed an effective cell response is probably the fastest way to treat critically ill individuals (297).…”
Section: Immune Cell-based Therapymentioning
confidence: 99%
“…Although our products were manufactured from a diverse group of donors, a limitation to this study is that we cannot evaluate for all possible HLA restricted responses. However, we and others have shown that even knowing a relatively restricted number of class I and class II restricted virus-specific responses provides important clinical information when evaluating virus-specific T cell products in a third party “off the shelf” setting ( 16 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“… 78 , 79 Other directions in future therapeutics include the use of monoclonal antibodies against the viral spike protein 80 and adoptive T cell therapy. Adoptive T cells with a chimeric antigen receptor or a T-cell receptor have been successfully developed against other viruses like Epstein barr virus 81 and severe acute respiratory syndrome coronavirus-1. 82 Use of adoptive T cell therapy may be particularly helpful in SOT recipients with COVID-19 in reducing the risk of serious complications and are in the developmental stage ( https://www.fiercebiotech.com/research/scientists-explore-using-engineered-t-cells-to-target-covid-19 ).…”
Section: Managementmentioning
confidence: 99%